Implementation of Religious Moderation Policies in the Islamic Education Curriculum to Prevent Radicalism and Strengthen Inclusivity in the Digital Era - Abdul Somad; Ahmad Basuni; Abd. Muis (Lembaga Penerbitan, Penelitian dan Pengabdian kepada Masyarakat, Institut Badri Mashduqi, 2026)
This study aims to analyze the implementation of religious moderation policies in the Islamic Education curriculum to prevent radicalism and strengthen students’ inclusivity in the digital era. The research employed a qualitative case study approach. Data were collected through interviews, observations, and documentation, and analyzed using data condensation, reduction, display, and conclusion drawing. Data validity was ensured through source triangulation, technique triangulation, and member checking. The findings indicate that religious moderation policies are implemented through the integration of moderation values into curriculum content, learning activities, and school culture. The integration of values such as tolerance, balance, and respect for diversity strengthens students’ inclusivity and critical digital literacy. The study also found that leadership commitment, teacher role modeling, curriculum integration, and an inclusive school environment support the implementation process. Meanwhile, exposure to radical online content and limited digital literacy remain significant challenges. The study concludes that implementing religious moderation within the Islamic Education curriculum is an effective strategy for preventing radicalism and fostering moderate, inclusive, and critical-minded students in the digital era